Local Perspectives on English Language Teaching in Private Tutoring in Thailand: Re-examining Roles and Implications - Charoenroop, Pattrawut (rEFLections, 2021)
Private tutoring has, over the past decades, been a key educational phenomenon for Thai college-bound students. having received both praise and condemnation. This qualitative case study shows that private English tutoring in Thailand has expanded beyond the ‘shadow education’ discussed by Bray (1999). Five tutor-student pairs were interviewed via Zoom video conference and the interviews were analyzed by theme. Results indicate the social, educational, and economic benefits of private education, as well as its far-reaching effects on personal growth, professional development, and life prospects. Concerns about educational inequality introduced by the tutoring industry, and its uneasy co-existence with mainstream education, are also discussed.